Effects of raloxifene and estradiol on bone turnover parameters in intact and ovariectomized rats - Canpolat, S.; Tug, N.; Seyran, A. D.; Kumru, S.; Yilmaz, B. (Springer, 2010)
This study was designed to investigate effects of raloxifene (RLX) and estradiol on bone formation and resorption in intact and ovariectomized (ovx) rat models. In the intact model, a total of 24 adult female rats were divided into three groups: Controls subcutaneously received saline alone. RLX (2 mg/kg) and estradiol (30 mu g/kg) were injected to two groups of animals for a period of 6 weeks at two daily intervals. In the second model, rats (n=24) were ovx and allowed to recover for a period of at least 3 weeks. Control group received vehicle alone. Remaining rats were divided into two groups and injected with RLX (2 mg/kg) and estradiol (30 mu g/kg) for 6 weeks. Urine samples were collected from all animals 24 h after the last drug administration. Urinary deoxypyridinoline (DPD) was measured by ELISA. Serum parathyroid hormone (PTH), calcitonin, and osteocalcin levels were measured by immunoradiometric method. Serum concentrations of alkaline phosphatase (ALP), Ca, and inorganic phosphate were determined by enzymatic-colorimetric method. Lumbar vertebrae (L2) of all animals were dissected out and processed for histopathological evaluation. Removal of ovaries significantly elevated urinary DPD levels (p<0.01) compared with intact controls. Treatment of both intact and ovx rats with estradiol resulted in significant decreases (p<0.01) in DPD values. RLX administration had no significant effect in the intact rats, but it remarkably reduced bone turnover in the ovx animals (p<0.001). Both estradiol and RLX produced conflicting effects on serum ALP, osteocalcin, and PTH levels in both animal models. These findings suggest that RLX exerts its protective effects by reducing bone resorption, similar to that of estradiol, in ovx rats.
Keywords: Raloxifene; Deoxypyridinoline; Bone turnover; Estradiol; Rat